Real Hypersurfaces with Many Simple Singularities - Westenberger, Eric (Revista Matemática Complutense, 2005)
In this paper we present constructions of real hypersurfaces with many simple singularities and deduce an asymptotical optimal existence result for hypersurfaces corresponding to T-smooth germs of the equisingular stratum. We proceed along the lines of [7] where analogous results were shown for the complex case.